Ruumiista miestä, tarinasta tulkintaa : oikeita miehiä - ja urheilijoita? - Tiihonen, Arto (2002)
In this dissertation, the author analyses his own and other men's body experiences in sport. This research derives from a phenomenological framework with additional links to the sociology of the body, life history, men's studies, autobiography and narrative studies. Through this analysis the author reflects on various changes within the social history of Finnish sport over the last decades. To achieve this, the author utilises a narrative approach to study men's sporting experiences. This book consists of fifteen articles which have been separated into three chapters. Chapter one provides a theoretical discussion of phenomenology and interpretive theory, while also outlining the researcher's ontological and epistemological position to "Narratives of the Self' as a contemporary qualitative research method for undertaking a sociological analysis of the body. Chapter two explores various sides of masculinity by giving voice to a range of men's experiences in sport. These stories are personal and historical in nature, thus enabling the reader to develop an emotional affinity as well as a critical understanding of the transitions men undergo in their lives. This includes, for example, the transitions men make from boyhood to manhood and even to fatherhood. In the third chapter, the author contextualises the key themes from chapters one and two to analyse a number of changes in Finnish sport. Changes that emphasise competition above participation, an increase in the use of sport science, a greater institutionalisation of the provision of sport and increased attention through the media. The body experiences and masculine sporting cultures considered in this dissertation have been studied within their natural setting, thus bringing a strong qualitative sensibility to this project. The author has also interpreted his subjects' sporting experiences in a storied manner. This "experiential data" consists of stories from the author's life as well as those of his "research partners"' (objects) and "thick" texts from selected cultural products. The central result of this dissertation is that manhood cannot be wholly understood without considering how men interpret their own body experiences, which they could have primarily come to know through their participation in sport subcultures. What it means to be a man, therefore, is connected to larger sociocultural changes within Finnish society. In addition, these results imply that one cannot speak intelligently about the development of Finnish sport without a sophisticated understanding of men's various body projects and their effect on masculinity. This dissertation offers many practical applications concerning masculine/feminine perspectives on the body, changes in Finnish sporting culture and the usefulness of autobiographical and narrative studies. Through narrativity, for example, it's possible to understand one's own experiences while also relating this knowledge to experts in the field. This could include assisting teacher's or coach's to discover their own significant body experiences while also helping them to identify how these experiences have influenced their own teaching or coaching practices, their relationship to their students and their concerns regarding issues connected to gender, the body and sexuality.